修形直齿锥形齿轮啮合特性研究 - 王祖兵; 方宗德; 苏进展 (Jixie chuandong)
A spur conical gear set with parabolic tooth profile modifications and arc tooth axial modifications can avoid the edge contact,and the gear set is robust against installation errors.The gear tooth surface can be generated by a imaginary rack cutter.The mathematical model of the gear is deduced by simulated the meshing kinematics between the rack cutter and the generated gear.According to the mathematical models,the tooth contact analysis model is established on the conditions of continuous tangency of two contact surface.The simulation shows that,the meshing performance of the gear set is improved by the decreasing of the sensitivity to installation error,and the edge contact is avoided.